Solar data logger - Azura, Ahmad (2009)
There are so many reasons for logging solar insolation for solar system. When planning to install a solar system, one must be able to predict the power output in order to determine the financial costs and benefits of the installation. Apart from that when planning an off grid solar electric power system, the output must be closely matched with the load so as to provide sufficient power without considerable waste. The proposed this report intends to enhance the use of solar Photovoltaic (PV)systems in University Malaysia Pahang by looking into the insolation value of the solar. I intend to build solar data logger. The objective of this project is to measure the voltage and current that will be produce from the photovoltaic panel. Later the data will be log to the memory and downloaded to the computer. The system is powered by small solar panel. When put out in sunlight the photovoltaic measure the insolation level of the solar. By using PIC18f455O1 it converts the analog input from the solar panel converted to digital that is stored in flash memory. Later the data will be display to LCD and downloaded to the computer. By using the visual basic program every time the system logs a data point, it also logs the time and date so that it will be analyzed in the future.